GOING GRAY? USING EXPERIENCE SAMPLING METHODS WITH OLDER CIVIC ENGAGEMENT EXEMPLARS. (11th November 2018) - Nakamura, J; Boeder, J; Graham, L
Abstract: This presentation discusses methodological strengths and limitations of using experience sampling methods (ESM) with an older exemplar population. As illustrated in the preceding papers and in this presentation, ESM provided rich information about the dynamics of civic engagement exemplars' experience and the ecology of their daily lives impossible to obtain with other methods. This study was conducted despite a number of apparent barriers. For example, the sample of civic engagement exemplars was dispersed across the country, precluding person-to-person walkthroughs. In addition, although technological advances enable ESM researchers to utilize increasingly sophisticated technology for data collection, there were also concerns as to whether the participant experience would be hindered by introducing novel technology to the sample. Lessons of general interest gleaned from both researchers and participants will be discussed and methods of addressing these issues will be described.